2019
DOI: 10.3390/polym11020253
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Phosphate-Imprinted PNIPAM/SiO2 Hybrid Particles and Their Phosphate Binding Property

Abstract: A SiO2 microsphere imprinted by phosphate ions was prepared with the use of phosphate ion as the template molecule and tetraethoxysilane as the precursor. Thereafter, the imprinted SiO2 microspheres were modified with 3-(trimethoxysilyl)propyl methacrylate (TMSPMA@SiO2), followed by introducing the double bond. In the presence of TMSPMA@SiO2, using N-isopropylacrylamide as monomer, and potassium persulfate as initiator, polymer/inorganic hybrid particles (PNIPAM/SiO2) were prepared. Fourier transform infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Therefore, it is of great signicance to develop efficient microgel adsorption materials and to remove excessive phosphate ions from water. 27,28 Hui et al 29 prepared polyvinyl alcohol hydrogel microspheres containing aluminum ions (Al 3+ ) in a internal network structure by a chemical crosslinking method. It was found that with an increase in AlCl 3 concentration and an extension of crosslinking time, the permeability of the hydrogel decreased, and the adsorption capacity for phosphate ions rst increased and then decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is of great signicance to develop efficient microgel adsorption materials and to remove excessive phosphate ions from water. 27,28 Hui et al 29 prepared polyvinyl alcohol hydrogel microspheres containing aluminum ions (Al 3+ ) in a internal network structure by a chemical crosslinking method. It was found that with an increase in AlCl 3 concentration and an extension of crosslinking time, the permeability of the hydrogel decreased, and the adsorption capacity for phosphate ions rst increased and then decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to develop efficient microgel adsorption materials and to remove excessive phosphate ions from water. 27,28…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] Due to the special structure, good hydrophilicity, abundant functional groups, and good biocompatibility, hydrogels can be widely used in the fields of controlled drug release, sensing, catalysis, adsorption, and separation. [36][37][38][39][40][41][42][43] Liu's group did extensive research work [44][45][46][47][48] on the preparation of the protein-based adhesive hydrogels and their biomedical applications in the wound healing and skin regeneration. For example, they fabricated the nonswelling protein-based coacervate adhesive hydrogels using electrostatic interaction of supercharged polypeptides with oppositely charged surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction mechanism between microgels and dye molecules follows a pseudo-second-order model and can be understood with equilibrium adsorption isotherms. The interaction of the related materials with dye molecules, , ions, proteins, and biomolecules has also been a research hotspot in recent years.…”
Section: Introductionmentioning
confidence: 99%